The effect of online project-based learning on metacognitive awareness of middle school students - Kalemkus, Fatih; Bulut-Ozek, Muzeyyen (Routledge Journals, Taylor & Francis Ltd, 2024)
The purpose of this research is to examine the effects of online project-based learning on students' metacognitive awareness. The participants of the research were 53 students attending 6th grade. The research was carried out using the mixed method approach and it was conducted with the action research model. Pre-test and post-test quantitative data were analysed with Paired-Samples T test in SPSS 22.0 package program. Semi-structured interviews were made with 10 of the research participants and the obtained qualitative interview data was analysed in the Nvivo software. According to the quantitative findings of the study, online project-based learning improved the students' metacognitive awareness. In accordance with the qualitative findings of the study, the categories of supervision, task, monitoring and self-awareness were formed under the theme of metacognitive awareness. In the supervision category the highest frequency was determined as the time-wasting prevention code, under the task category the highest frequency was the information access code, under the monitoring category the highest frequency was the self-evaluation code for learning, and under the personal awareness category the highest frequency was the evaluation code for learning. It was concluded that the qualitative findings of the research supported its quantitative findings.
Keywords: Online project-based learning; metacognitive awareness; metacognition; middle school students